Progress and trends of optical microfiber-based biosensors - Mustapha Kamil, Yasmin; Abu Bakar, Muhammad Hafiz; Zainuddin, Nurul Hida; Yaacob, Mohd Hanif; Mahdi, Mohd Adzir (MDPI, 2023)
Biosensors are central to diagnostic and medicinal applications, especially in terms of monitoring, managing illness, and public health. Microfiber-based biosensors are known to be capable of measuring both the presence and behavior of biological molecules in a highly sensitive manner. In addition, the flexibility of microfiber in supporting a variety of sensing layer designs and the integration of nanomaterials with biorecognition molecules brings immense opportunity for specificity enhancement. This review paper aims to discuss and explore different microfiber configurations by highlighting their fundamental concepts, fabrication processes, and performance as biosensors.